Rapid method for the determination of 14 isoflavones in food using UHPLC coupled to photo diode array detection. (15th November 2015) - Shim, You-Shin; Yoon, Won-Jin; Hwang, Jin-Bong; Park, Hyun-Jin; Seo, Dongwon; Ha, Jaeho
Highlights: Establishment of rapid and simple pretreatment method for 14 types of isoflavones. Establishment of rapid detection method for 14 types of isoflavones using UHPLC/PDA. Established method was validated through precision, accuracy and linearity. Application test for various real samples such as beans and its processed products. Abstract: A rapid method for the determination of 14 types of isoflavones in food using ultra-high performance liquid chromatography (UHPLC) was validated in terms of precision, accuracy, sensitivity and linearity. The UHPLC separation was performed on a reverse-phase C18 column (particle size 2 μm, i.d. 2 mm, length 100 mm) using a photo diode array detector that was fixed to 260 nm. The limits of detection and quantification of the UHPLC analyses ranged from 0.03 to 0.33 mg kg −1 . The intra-day and inter-day precision of the individual isoflavones were less than 11.77% and calibration curves exhibited good linearity ( r 2  = 0.99) within the tested ranges. These results suggest that the rapid method used in this study could be available to determine of 14 types of isoflavones in a variety of food such as soy bean, black bean, red bean and soybean paste.